Recovery using "float" from high intensity stress on growth hormone-like molecules in resistance trained men. (December 2020) - Kraemer, William J.; Caldwell, Lydia K.; Post, Emily M.; Beeler, Matthew K.; Dickerson, Ryan M.; Kennett, Mary J.; Volek, Jeff S.; Maresh, Carl M.; Hymer, Wesley C.
Abstract: Objective: The purpose of this study was to examine the influence of a novel "floatation-restricted environmental stimulation therapy" (floatation-REST) on growth hormone responses to an intense resistance exercise stress. Design: Nine resistance trained men (age: 23.4 ± 2.5 yrs.; height: 175.3 ± 5.4 cm; body mass: 85.3 ± 7.9 kg) completed a balanced, crossover-controlled study design with two identical exercise trials, differing only in post-exercise recovery intervention (i.e., control or floatation-REST). A two-week washout period was used between experimental conditions. Plasma lactate was measured pre-exercise, immediately post-exercise and after the 1 h. recovery interventions. Plasma iGH was measured pre-exercise, immediately-post exercise, and after the recovery intervention, as well as 24 h and 48 h after the exercise test. The bGH-L was measured only at pre-exercise and following each recovery intervention. Results: For both experimental conditions, a significant ( P ≤ 0.05) increase in lactate concentrations were observed immediately post-exercise ( 14 mmol L-1) and remained slightly elevated after the recovery condition. The same pattern of responses was observed for iGH with no differences from resting values at 24 and 48 h of recovery. The bGH-L showed no exercise-induced changes following recovery with either treatment condition, however concentration values were dramatically lower than ever reported. Conclusion: The use of floatation-REST therapy immediately following intense resistance exercise does not appear to influence anterior pituitary function in highly resistance trained men. However, the lower values of bGH suggest dramatically different molecular processing mechanisms at work in this highly trained population. Highlights: Growth hormone-like molecules not affected by a novel floatation-REST therapy. Dramatically lower bioactive growth hormone in highly resistance trained men. Highly resistance trained men appear to process bioactive growth hormone differently.